PENINGKATAN PRODUKSI ASI MELALUI MASASE PAYUDARA - Rizki Oktaviani; Dinar Perbawati (Jurnal SADEWA, 2024)
Breast milk is a good natural food for babies, practical, economical, and easy to digest. The marmet technique is a technique of expressing breast milk manually by hand which stimulates the mother's milk glands to produce more milk. The low coverage of babies who receive exclusive breastfeeding in the working area of the Ajung Health Center and the targets set by the Jember District Health Office have not achieved. The purpose of this service is to socialize giving breast massage using the marmet technique to increase milk production for postpartum mothers in the working area of the Ajung Health Center. The socialization target for postpartum mothers is 30 people who are divided into two groups, namely 15 intervention groups and 15 control groups. Of the 30 people who took the pre-test to the post-test, it was found that most of the milk production had increased. Based on the results of community service, it can be said that the use of the marmet technique is one of the efforts to increase the coverage of exclusive breastfeeding so that it reaches the set targets.